INVESTIGATION OF THE EFFECT OF ADDING NANO MATERIAL INTO THE CLAY SOIL ON PERMEABILITY AND TREATMENT - Ozcoban, Mehmet Sukru; Demirkol, Guler Turkoglu; Armagan, Bulent; Demir, Nadire; Tufekci, Nese (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2022)
In this study, the permeability and treatment of the clay soil sample were examined experimen-tally by passing the leachate through the reactors by adding different nanomaterials (iron oxide, aluminum oxide) with varying amounts to the clay soil sample. For this reason, the wastewater sample collected from Kemerburgaz - Odayeri Regular Storage Area in Istanbul, European side and the clay soil (kaolin) from the company, Esan Eczacibasi Industrial Raw Materials Ind. and Trading Inc. was used. Since kaolin was clay soil and pulverized, it was taken from the company and no treatment was applied. At the end of this study, it was found that the nanomaterial which most decreased the permeability and highest removal rate of the clay soil was aluminum oxide.
Keywords: HYDRAULIC CONDUCTIVITY; LANDFILL LEACHATES; COMPACTED CLAYS; REMOVAL RATE; CONTAMINANTS; TRANSPORT; MIGRATION; Environmental Sciences & Ecology